A Preliminary Study on the Characteristics of Lime-Based Mortars with Egg White Addition. Issue 8 (3rd August 2022) - Zhang, Kun; Wang, Liqin; Tie, Fude; Yang, Fuwei; Liu, Yan; Zhang, Yue
ABSTRACT: The present study focused on the characteristics of lime-based mortars with egg white addition prepared according to a historic Chinese recipe. Results suggested that under dry curing condition, the addition of egg white into mortars could decrease water absorption and increase surface hardness and compressive strength. Hardness and strength values of mortars cured under humid condition, however, were compromised by the egg white addition. Analyses results showed that under dry curing, egg white could inhibit carbonation and form amorphous calcium carbonate in the specimens, while under humid curing, egg white would impede hydration reactions and increase mortar pore size.